The war on poverty after 40 years: A Minskyan assessment - Stephanie A. Bell; L. Randall Wray (Levy Economics Institute of Bard College, 2004)
Twenty to 25 years ago, a debate was under way in academe and in the popular press over the War on Poverty. One group of scholars argued that the war, initiated by Presidents Kennedy and Johnson, had been lost, owing to the inherent ineffectiveness of government welfare programs. Charles Murray and other scholars argued that welfare programs only encouraged shiftlessness and burdened federal and state budgets. In recent years, despite the fact that the extent of poverty has not significantly diminished since the early 1970s, the debate over poverty has seemingly ended. In a country in which middle-class citizens struggle to afford health insurance and other necessities, the problems of the worst-off Americans seem to many remote and less than pressing. Moreover, the welfare reform bill of 1996 has deflected much of the criticism of the welfare state by ending the individual-level entitlement to Aid to Families with Dependent Children benefits (now known as Temporary Assistance to Needy Families) and putting time limits on welfare recipiency, among other measures.
Keywords: 330; Armutspolitik; USA